Efforts in improving Arabic and Islamic Learning Motivation at Tbong Khmum Muhammadiyah Education Center - Lorenza, Vivi (Universitas Muhammadiyah Sumatera Barat, 2022)
Strong motivation is a factor influencing results, as well as in learning, strong motivation from students will bring maximum results. Students at Tbong Khmum Cambodia Muhammadiyah Education Center still have low motivation in learning Arabic and Islamic sciences. Therefore, this study aims to reveal the steps taken by teachers in improving the motivation to learn Arabic and Islam. The study was carried out with a qualitative approach. To increase Arabic and Islamic learning motivation at the Muhammadiyah Education Center, first, provide an understanding of the importance of Arabic and Islam, second, create and choose learning methods and media, third, complete learning facilities and infrastructure, fourth, provide an assessment. From these four steps, this study recommended that Arabic and Islamic teachers should further maximize efforts to increase the motivation of students so that learning outcomes are expected to be achieved optimally.